Adlai-Enriched Maja Blanca as a Fiber-Enhanced Functional Filipino Coconut Pudding: Product Development and Consumer Acceptability - Revadillo, Joseph Anthony; Abellana, Ephraimuel Jose (JPAIR Multidisciplinary Research, 2026)
This study developed and evaluated Adlai-enriched Maja Blanca as a fiber-enhanced functional Filipino coconut pudding. It determined the respondents’ demographic profile, the estimated nutritional profile of the formulations, their sensory acceptability, and the formulation recommended as a standardized recipe. The study used a product development and descriptive consumer acceptability design. Three formulations were prepared: a control with 0% Adlai flour, a 40% Adlai flour substitution, and a 60% Adlai flour substitution. Eighty respondents from the Philippine Women’s University evaluated the samples using a 9-point hedonic scale in terms of appearance, aroma, taste, texture, and overall acceptability. The estimated nutritional profile per 30 g serving was reviewed by a Licensed Nutritionist-Dietitian. Results showed that the 60% Adlai formulation had the most favorable estimated nutritional profile, with slightly lower energy and carbohydrate values and slightly higher protein and total dietary fiber content. All formulations were rated as Like Moderately across sensory attributes. The 60% Adlai formulation obtained the highest mean scores in appearance, taste, and overall acceptability. The novelty of the study lies in the use of Adlai flour as a partial substitute for cornstarch in a traditional Filipino dessert, contributing to functional food development using a locally relevant and underutilized grain. Based on the combined nutritional and sensory results, the 60% Adlai-enriched Maja Blanca formulation is recommended as the standardized recipe. The findings may support future foodservice application, culinary education, community nutrition initiatives, and small-scale product development.